2009
DOI: 10.1111/j.1574-695x.2009.00550.x
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence ofFusobacterium variumin ulcerative colitis patients in Japan

Abstract: The etiology of ulcerative colitis (UC) is unknown, while an exacerbating factor of this disease is associated with infectious agents. Recently, Fusobacterium varium has been found in the mucosa of a significant number of patients with UC. The aim of this study was to estimate the prevalence of F. varium infection based on serology, evaluate the relationship between F. varium seropositivity and UC, and determine the clinical characteristics of infected UC individuals. Seropositive patients were determined by i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 22 publications
0
12
0
1
Order By: Relevance
“…There is also an established role for the gut microflora in the promotion of IBD exacerbation (1). Over the past decade, several bacterial pathogens have been implicated as contributing or even causal factors in IBD, including Mycobacterium paratuberculosis (5), adherent-invasive E. coli (38), and Fusobacterium varium (32,34). We have previously shown an increased recovery of highly invasive isolates of F. nucleatum from the gastrointestinal mucosae of CD patients compared to those of control colon cancer screen patients (40).…”
Section: Discussionmentioning
confidence: 99%
“…There is also an established role for the gut microflora in the promotion of IBD exacerbation (1). Over the past decade, several bacterial pathogens have been implicated as contributing or even causal factors in IBD, including Mycobacterium paratuberculosis (5), adherent-invasive E. coli (38), and Fusobacterium varium (32,34). We have previously shown an increased recovery of highly invasive isolates of F. nucleatum from the gastrointestinal mucosae of CD patients compared to those of control colon cancer screen patients (40).…”
Section: Discussionmentioning
confidence: 99%
“…Using immunoblotting with a F varium antigen Minami et al found positive signals with sera from 45 (40.2%) of 112 UC patients versus 20 (15.6%) of 128 healthy controls (p<0.01). Seropositive UC patients were more likely to have clinically severe disease than seronegative UC patients and the disease location in seropositive patients was more extensive than in seronegative patients 7. Finally, a 2-week triple antibiotic therapy to which F varium is susceptible (tetracycline, metronidazole and amoxicillin) produced improvement, remission and steroid withdrawal in active UC more effectively than a placebo 8…”
mentioning
confidence: 95%
“…Many authors follow a 'candidate bug approach' concentrating efforts on one micro-organism such as mycobacteria, Clostridium difficile , Helicobacter sp., Listeria , strains or groups of Escherichia coli, and fusobacteria [4][5][6][7][8][9][10][11][12] . Potentially protective microbes have also been studied, including lactobacilli, bifidobacteria and, more recently, Faecalibacterium prausnitzii [13][14][15][16] .…”
Section: Composition Of the Microbiota In Patients With Ibdmentioning
confidence: 99%